Challenges of Storage in Large Power Systems - Gómez-Ramírez, Gustavo A. (2021)
Fossil fuel-based electric generation is a contributor to air pollution in the world. In this regard, storage provides a viable specially if it is combined with solar energy and wind generation. Storage also represents a major challenge for the traditional criteria for planning the power system, which its generated with hydro and non-renewable generation as Central America case. This article reviews literature in loadability, frequency regulation and control, stability, economic issues, reliability, harmonics and power quality and resilience applied to power systems. It presents a simulation using ETAP to analyze voltage profiles considering storage for El Salvador Power System (ESPS). The result shows a significant contribution in to enhance the voltage profiles and voltage regulation after failed. Opportunities also arise when storage is considered as potential ancillary service providers that can help to stabilize the grid under faulty situation or to mitigate the power generation variability of non-traditional renewable power sources such as wind and solar energy in Central America Power System. The present paper provides an overview of the major challenges of storage to large power systems.